Hubungan Persepsi Terhadap Teknik Statistik dengan Minat Melakukan Penelitian Kuantitatif pada Mahasiswa Fakultas Dakwah IAIN Purwokerto - Amirotun Sholikhah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2017)
Background of this study is a tendency of quantitative approach which is rarely encountered during studentâ€™s thesis of Dakwah Faculty IAIN Purwokerto. This is partly due to the usage of statistical techniques as the analysis tools. This study is a survey research, conducted in random sampling techniques with 38 respondents. The data is collected by using observation, questionnaire, interview and documentation techniques. The data is analyzed and calculate using Pearsonâ€™s Product Moment correlation procedures in Microsoft Excell and SPSS. Conclusion of the study is that â€œThere is no correlation between the perception of statistical techniques and interest in using quantitative research towards student of Dakwah Faculty IAIN Purwokertoâ€, with the result of rxy, 0,247, as interpreted as a low correlation. The result is then consulted with Product Momentâ€™s r table and it shows that the value of rxy is less than on the r table, both in 5% and 1 % significance level. There are lots of them have perceptions that statistical procedures are difficult and so they have less interest in conducting final thesis using quantitative methodology, with the reason that the research problem is not suitable with the quantitative methods. They have hope of assistance from lecturer or possibility in using SPSS techniques.